PREDIKSI KEBANGKRUTAN PADA BANK BUMN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Muhammad Salman; Catur Wulandari (Fakultas Ekonomi Universitas Negeri Medan, 2021)
The research was conducted with the aim of knowing the prediction of the potential for bankruptcy of the four State-Owned Enterprises (BRI, BNI, Bank Mandiri and BTN) using the Altman Z-Score, Springate and Grover G-Score models. The data analysis method used a prediction model for the occurrence of bankruptcy consisting of the Altman Z-Score, Springate and Grover G-Score. The results showed that the prediction of bankruptcy (financial distress) using the Altman Z Score model was obtained from 2015-2019 for the four State-Owned Enterprise Banks (BRI, BNI, Bank Mandiri and BTN) as a whole obtained Z Score between 1.42-1 88 or at the criteria (cut off) Z <181 has the potential to go bankrupt and 1.81 <Z <2.99 gray area. Meanwhile, based on the Springate model from 2015-2019, the four State-Owned Enterprises (BRI, BNI, Bank Mandiri and BTN) overall obtained a Springate of 1.95 - 44.08 and were in the criteria (cut off) S> 0.862 and can be declared as not potentially bankrupt (healthy). Then based on Grover, it was obtained from 2015-2019 in the four State-Owned Enterprise Banks (BRI, BNI, Bank Mandiri and BTN) as a whole obtained a G Score of 1.71 - 2.15 and were in the criteria of G ≥ 0.01 or no potential bankrupt (healthy). The results showed that the Altman Z Score model has a better value than Springate and Grover because the number of ratios is more so that it can predict bankruptcy better